Implementing Microsoft Dynamics 365 Business Central on-premise : explore the capabilities of Dynamics NAV 2018 and Dynamics 365 Business Central and implement them efficiently /: explore the capabilities of Dynamics NAV 2018 and Dynamics 365 Business Central and implement them efficiently. (2018) - Stefanetti, Roberto; Chow, Alex
No abstract available